Toxicological effects of the environmental pollutant perfluoronanoic acid on the ground-dwelling arthropod Solenopsis invicta - Wenxuan Wang; Mingrong Liang; Yangting Ou; Xiangrui Wang; Yunbo Song; Huimei Chen; Jingxin Hong; Yuling Liang; Yongyue Lu (Ecotoxicology and Environmental Safety)
Perfluorononanoic acid (PFNA), widely employed in surfactants, coatings, plastics, corrosion inhibitors, and fire-extinguishing agents, is less regulated than PFOS or PFOA but displays higher bioaccumulation and potential toxicity. Most toxicity assessments have focused on mammals, fish, and algae, with limited research on ground-dwelling arthropods, especially ants. Here, we examined PFNA’s toxic effects on red imported fire ants (RIFAs), a prevalent ground-dwelling species in South China. Stomach and contact toxicity experiments revealed that PFNA significantly reduced RIFA viability, with poisoning severity correlating positively with both dose and exposure duration. PFNA inhibited key behaviors—including aggregation, climbing, grasping, crawling, and excavation—and impacted survival. For instance, after 12 hours at 0.12 mg/g PFNA, large and medium workers excavated only 0.136 g and 0.064 g of quartz sand, respectively, significantly less than controls. Lethal concentrations (LC50) decreased over time, falling to 53.089 mg/L by day 7. Moreover, PFNA exhibited sublethal effects by curtailing feeding and raising mortality rates; in 100 mg/L and 500 mg/L treatments, cumulative mortality reached 30.70 % and 53.60 %, respectively, by day 15. The 500 mg/L group also showed reduced consumption of sugar water and locusts from day 12–20. Elevated superoxide dismutase (SOD) and catalase (CAT) activities at higher PFNA concentrations indicated oxidative stress in RIFAs. Collectively, these findings demonstrate PFNA's concentration-dependent toxic and repellent effects on RIFAs, emphasizing the need for further research on PFNA toxicity in ground-dwelling arthropods and the potential of RIFAs as a bioassay species for pollutant assessment.